(untitled) (Journal of Science and Technology, 2016)
The causal factors and magnitude of malformation of cleft lip (hare lip) amongst some inhabitants of Wudoaba, a village in south-eastern Ghana was investigated because most women visiting the night market in the village claimed some of their counterparts had cleft lip (hare-lip) while some spoke through their nose. The market is called a “ghost market” due to the nasal sound produced by the speech of the people. Using purposive and accidental random sampling technique and questionnaire interviews, some citizens, traditional rulers and opinion leaders were interviewed. Of the 13 interviewed three were females and 10 males with ages between 20 and 70. Secondly, 11 of the13 respondents were married, with one being single and one co-habiting. Out of the 12 that were “married”, five were not related, six were cross-cousins and one was a linear-cousin. Sixteen of the market women had “nasal ghost speeches” and nine had cleft lips. The market women claimed that about 20 of their colleagues also had cleft lips. Wudoaba may be cleft endemic and the cause of malformation could be genetic. Most of the victims were treated as social outcasts hence the “cover” night markets. A vigorous health education awareness campaign is needed and for those with the disease to undergo plastic surgery.